Parental Mental Health, Fathers' Involvement and Bedtime Resistance in Infants - Benedetta Ragni; Simona De Stasio; Daniela Barni; Simonetta Gentile; Rosaria Giampaolo (BMC, 2019)
Abstract Background Around the age of 6 months, difficulties in settling to sleep and frequent night awakenings are generally occurring in 20 to 30% of infants. According to the transactional model parental factors can play a significant role in influencing infant sleep development. The purpose of the current study was to explore the combined effect of infants' factors (temperament and sleep onset problems), and parental factors (parental mental health in terms of post-partum affective disorders, consistent bedtime routines and fathers' involvement at bedtime), on infant bedtime difficulties (e.g. fussing, crying or protesting), including both maternal and paternal perspectives. Methods Sixty Italian intact two-parent families of infants (34 boys and 26 girls) ageing from 8 to 12 months (M = 10.73, SD = 2.54) were enrolled in the study. The parents filled out self-report questionnaires to measure the aforementioned variables. To investigate which infant and parental factors predicted infants' bedtime difficulties, two multiple linear regressions (MR), one for fathers and one for mothers, and relative weight analyses (RWA) were conducted. Results With regard to infants' bedtime difficulties reported by fathers (R2 = .35) they were explained by infant involvement in constant bedtime routines (β = −.35, p = .030) and paternal involvement at bedtime (β = −.45, p = .007). Instead infants' bedtime difficulties reported by mothers (R2 = .32) were explained by minutes the child taken to fall asleep (β = .24, p = .04), infant involvement in constant bedtime routines (β = −.31, p = .01) and bedtime paternal involvement (β = −.27, p = .05). Conclusions The main results of this study emphasized the protective role of consistent bedtime routines and bedtime paternal involvement in reducing infants' bedtime difficulties perceived both from mothers and fathers. Future research could help to raise awareness and improve understanding of the familial influences on children's sleep, providing recommendations for educating families, school professionals, healthcare providers, and the general public on risk and protective factors that could play a meaningful role in infants and children's developing sleep patterns.